Unique actinomycin D binding to self-complementary d(CXYGGCCY′X′G) sequences: duplex disruption and binding to a nominally base-paired hairpin - Chen, Fu-Ming (Oxford University Press, 2003)
Actinomycin D (ACTD) has been shown to bind weakly to the sequence -GGCC-, despite the presence of a GpC site. It was subsequently found, however, that d(CATGGCCATG) binds relatively well to ACTD but exhibits unusually slow association kinetics, contrary to the strong-binding -XGCY- sites. In an effort to elucidate the nature of such binding and to delineate the origin of its interesting kinetic behavior, studies have now been extended to include oligomers with the general sequence motifs of d(CXYGGCCY′X′G)(2). It was found that analogous binding characteristics are observed for these self-duplex decamers and comparative studies with progressively base-truncated oligomers from the 5′-end led to the finding that d(GGCCY′X′G) oligomers bind ACTD considerably stronger than their parent decamers and exhibit 1:1 drug/strand binding stoichiometry. Melting profiles monitored at the drug spectral region indicated additional drug binding prior to the onset of eventual complex disruptions with near identical melting temperatures for all the oligomers studied. These results are consistent with the notion that the related oligomers share a common strong binding mode of a hairpin-type, with the 3′-terminus G folding back to base-pair with the C base of GGC. A binding scheme is proposed in which the oligomers d(CXYGGCCY′X′G) exist predominantly in the duplex form and bind ACTD initially at the central GGCC weak site but subsequently disrupt to accommodate the stronger hairpin binding and thus the slow association kinetics. Such a mechanism is supported by the observation of distinct biphasic fluorescence kinetic traces in the binding of 7-amino-ACTD to these duplexes.